A New Algorithm Based Graph-Search for Workflow Verification - Zhongjun Du; Zhengjun Dang (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
In many circumstances, the structural conflicts in workflow processes lead to malfunctioning of workflow management systems. So the conflicts should be detected and resolved before workflow processes are actually put into execution. Up to now, there is still no effective algorithm which can be able to detect out the structural conflicts both in the workflow without loop and in the workflow with loop. This paper proposed a new algorithm which transforms the loop in the workflow to an acyclic sub-graph and can detect out the structural conflicts in the workflow even with loop.